A Perspective on Reversibility of Tendinosis-Induced Multi-Level Adaptations - Kulig, Kornelia; Chang, Yu-Jen; Ortiz-Weissberg, David (Frontiers in Physiology, 2020)
Achilles tendinopathy is a well-known pathology that can display interindividual variations in chronicity, symptom presentation, and tendon morphology. Furthermore, symptoms may fluctuate within an individual throughout the stages of the pathology. Although pain is often used as a marker of condition severity, individuals may not consistently report pain due to periods of remission. Persons with tendinosis, which is characterized by advanced morphological alterations, have shown persistent changes in neuromechanics that indicate adaptations in the sensory-motor and the central nervous systems. The current treatment strategy involves repetitive resistance exercise aiming to achieve recovery of lost function. This treatment approach, however, has gauged such functional recovery through symptom relief and return to sport, which, in our opinion, may not suffice and may not prevent symptom recurrence or tendon rupture. In this physiologically-informed perspective, we briefly review what is currently known about the consequences of Achilles tendon degeneration and examine the topic of reversing these changes. Shortcomings of contemporary treatment strategies are discussed and we therefore call for a new paradigm to focus on the whole-body level, targeting not only the tendon but also the reversal of the neuromotor control system adaptations.